Criminal Responsibility for Consumer Protection for Perpetrators of Illegal Cosmetics Crime in North Sumatra (Case Study Number: 3405/Pid.Sus/2018/Pn.Mdn) - Marudut Hasiholan Gultom; M. Maswandi; Rizkan Zulyadi (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2026)
Criminal liability is a legal obligation imposed on a person for a criminal act he or she commits, which is based on the existence of fault (intentionality or negligence) and the ability to be legally responsible. In English, namely criminal responbility, the Greek word cosmetics means the skill of decorating. In the Great Indonesian dictionary, it is related to beauty. Criminal responsibility has a community relationship as a social control so that they do not commit criminal acts. In this issue, the author includes a formulation of the problem of how to regulate criminal liability for perpetrators of illegal cosmetics crimes in Indonesia. The research was conducted to find out the actions of the perpetrators of distributing cosmetics without a distribution permit. Based on the above explanation, the author draws the conclusion that cosmetics is that certain substances are used to make up and have an effect on the appearance of normative laws by researching literature materials, cosmetics are a basic need, especially women, it is not surprising that the demand for cosmetic products is increasing and variing. Criminal law regulations for perpetrators of the act of distributing cosmetics without a distribution permit are regulated in Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection Article 62 paragraph (1) and Law Number 36 of 2009 concerning health. Criminal liability for the perpetrators of the act of distributing cosmetics without a distribution permit is appropriate because it meets subjective elements.